2006
DOI: 10.1093/beheco/arl036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for a causal effect of pair-bond duration on reproductive performance in oystercatchers (Haematopus ostralegus)

Abstract: Many studies have suggested that reproductive performance improves during the pair-bond, which might explain why individuals remate with the same partner in many species. However, discussion exists about whether the association between reproductive performance and pair-bond duration that is reported in these studies reflects a causal relationship. Usually it is unclear whether a positive association is caused by pairs improving during their pair-bond or by high-quality pairs staying together for longer. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 39 publications
8
90
1
Order By: Relevance
“…As the frequency of flooding events increases we would expect directional selection to favour higher nest elevation, working via the fitness component of nest success. Encouragingly, our study population has shown an increase in mean nest elevation over time at half the rate of change seen in maximum high tide [35], providing evidence that changing nest elevation as a response to flooding may be possible.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…As the frequency of flooding events increases we would expect directional selection to favour higher nest elevation, working via the fitness component of nest success. Encouragingly, our study population has shown an increase in mean nest elevation over time at half the rate of change seen in maximum high tide [35], providing evidence that changing nest elevation as a response to flooding may be possible.…”
Section: Introductionsupporting
confidence: 51%
“…(d) Alternatives to phenotypic plasticity As H. ostralegus is a long-lived species, we initially hypothesized that phenotypic plasticity in nest-site selection would provide the most likely explanation for the increasing mean nest elevation observed within our population [35]; however, our current analyses provide no evidence to support this prediction, compelling us to consider alternative mechanisms. Micro-evolution in nest elevation is possible, although the long generation time of our study species makes this explanation unlikely.…”
Section: (C) Counter-acting Selection Pressuresmentioning
confidence: 82%
See 1 more Smart Citation
“…Female aggression towards male intruders may function to defend their mates against eviction by prospecting males, which would be advantageous if staying with current partners confers some benefit, such as increased reproductive success with a familiar mate (e.g. van de Pol et al 2006). Similar to non-territorial females, encounters with non-territorial males should be more prevalent during pre-breeding, leading to the prediction that female aggression should be more intense then than during breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed in male vertebrates, territorial aggression is differentially hormonally regulated depending on the seasonal context (breeding versus nonbreeding seasons, e.g. Caldwell et al 1984;Soma et al 2000;Canoine & Gwinner 2002;Wingfield & Soma 2002;Buck & Barnes 2003;Hau et al 2004). Evidence is scanty, but different endocrine mechanisms may regulate breeding and non-breeding territorial aggression in females as well (Schwabl 1992;Hau et al 2004;Scotti et al 2007).…”
Section: Introductionmentioning
confidence: 99%